The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1186/s12909-018-1441-6
|View full text |Cite
|
Sign up to set email alerts
|

Self–handicapping among nursing students: an interventional study

Abstract: Background Self-handicapping is an effective defense strategy in an individual’s behavior that leads to weak performance in different situations like education. This study aimed to investigate how training problem solving skills affected the rate of self-handicapping among nursing students. Methods This interventional study was done in Jahrom, Fars province, Iran during 2016–2017. Totally, 90 nursing students were selected among those admitted from 2013 to 2016 using st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…Self-handicapping, emerging as a big obstacle to realize one's potential and to succeed, has many negative associations with academic life, health, and psychological well-being (Barutçu,2020). During the COVID-19 pandemic, using self-handicapping strategies is one of the important and effective factors in students' psychological health that has important consequences, such as weak academic performance and lack of efforts (Zarshenas et al,2019). In order to make students better get through this special period, it is worth studying their selfhandicapping.…”
Section: Introductionmentioning
confidence: 99%
“…Self-handicapping, emerging as a big obstacle to realize one's potential and to succeed, has many negative associations with academic life, health, and psychological well-being (Barutçu,2020). During the COVID-19 pandemic, using self-handicapping strategies is one of the important and effective factors in students' psychological health that has important consequences, such as weak academic performance and lack of efforts (Zarshenas et al,2019). In order to make students better get through this special period, it is worth studying their selfhandicapping.…”
Section: Introductionmentioning
confidence: 99%
“…This often resulted in consultations being dominated by their parents 40. The intervention studies often proposed health information through theoretical and/or practical or skill-based presentations, including various topics related to MSDs 30 33–36 38 46 51 55–62. Sessions varied between learning about anatomy, risk factors, prevention techniques, workshops with practical ergonomic exercises, comic books explaining disease-related information and benefits of treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Fourteen studies used self-reported questionnaires to measure how adolescents consider changes in their health behaviour 30 32 37 38 46 48 49 55–60 65. For example, one study showed improved self-efficacy scores, as the adolescents expressed confidence that they would change their exercise habits after receiving health-related information 46.…”
Section: Resultsmentioning
confidence: 99%
“…The present study adopted the term academic self-handicapping which was used to explain many of the academic aspects related to learner's personality. It revealed when the learner faces obstacles that prevent him from achieving his goals (Zarshenas et al, 2019). Academic self-handicapping is defined as "students' use of various strategies to justify their academic failures, as a means by which the relationship between academic performance and personality can be blurred" (Akin & Abaci, 2011, p. 33).…”
Section: Theoretical Frameworkmentioning
confidence: 99%